Antibiotics Against Endocarditis – Past, Present and Future (Experimental Data) - Jacqueline, Cédric; Amador, Gilles; Batard, Eric; Mabecque, Virginie Le; Potel, Gilles; Caillon, Jocelyne (IntechOpen, 2012)
None